PTH-112 Infliximab Promotes Steroid free Remission in Patients with Chronic Active Ulcerative Colitis– a UK Single Centre Experience. (4th June 2013) - Shepherd, T C; Greveson, K; Cronin, E; Erian, G; Jaboli, F; Despott, E; Hamilton, M; Murray, C
Abstract : Introduction: The role of infliximab (IFX) in the salvage treatment of acute severe ulcerative colitis (UC) is well established and both licenced and approved in the UK. Studies have demonstrated that IFX IS effective in the treatment of chronic steroid dependent/refractory UC (1) In the UK IFX is not routinely approved for the treatment of chronic steroid-dependent colitis. Our aim was to assess the long-term outcomes of patients treated with IFX for chronic active UC in a single UK IBD centre. Methods: A retrospective single centre review was undertaken of patients with severe active UC who received IFX (5mg/kg) between May 2008 and April 2012. Clinical remission was defined as complete steroid withdrawal, normalisation of bowel frequency and absence of blood with defecation. Treatment with IFX was only continued if steroid free remission was maintained. Results: 23 patients were included.10 (43%) of patients were treated with induction therapy only (0, 2 & 6 wks) due to funding constraints. 6 (60%) of this group were not on thiopurines, having been either unresponsive or intolerant. 5 (50%) entered clinical remission-median follow up 18 months (IQR 15–25) & 2 (20%) had colectomy. 13 (57%) were treated with induction and maintenance therapy. Of these 7 (85%) were already established on a thiopurine without clinical response. All 13 (100%) entered clinical remission as defined, median follow up 21 months (IQR 11–26). 1 patient required dose escalation to 10mg/kg. None of the patients in the maintenance group were admitted during this time. No significant side effects were reported in either group. Conclusion: In our patients treated with IFX for chronic active UC, IFX maintenance therapy appears to have more sustained steroid free remission rates compared with induction therapy only. All patients treated this way avoided colectomy, hospital admission and had complete steroid free remission during follow-up. Experience of maintenance IFX therapy for UC in the UK is limited due to funding constraints but our data confirms the efficacy of this approach in carefully selected patients the response rate may be higher than in other published series. Disclosure of Interest: None Declared. Reference: Rutgeerts P, Sandborn WJ, Feagan BG, et al. Infliximab for induction and maintenance therapy for ulcerative colitis. N Engl J Med. 2005; 353:2462–2476.